Trabecular Bone Remodeling after Lateral Lumbar Interbody Fusion: Indirect Findings for Stress Transmission between Vertebrae after Spinal Fusion Surgery - Naoki Segi; Hiroaki Nakashima; Sadayuki Ito; Jun Ouchida; Ryotaro Oishi; Ippei Yamauchi; Yuichi Miyairi; Yoshinori Morita; Mikito Tsushima; Hiroyuki Tomita; Kazuaki Morishita; Kazuma Ohshima; et al. (Spine Surgery and Related Research)
Introduction: After posterior lumbar interbody fusion (PLIF), trabecular bone remodeling (TBR) occurs in the vertebral body. This study aimed to investigate whether imaging findings obtained with PLIF are applicable to lateral lumbar interbody fusion (LLIF). Methods: A total of 53 cases who underwent one- or two-level LLIF with polyether ether ketone cage and posterior spinal fixation/fusion (PSF) were retrospectively included in this study. TBR, vertebral endplate cyst (VEC), facet union, and pseudarthrosis were investigated on computed tomography (CT) images at 3 months, 1 year, and 2 years postoperatively. Of the 53 patients, 36 (68%) who underwent CT examination at approximately 5 years postoperatively were subanalyzed. Results: TBR was commonly observed anterior to the cage on CT sagittal images. The TBR-positive rate was 21%, 67%, and 73% at 3 months, 1 year, and 2 years postoperatively, respectively. The 3-month TBR-positive segments showed significantly less VEC (0% vs. 29%, P=0.029) at 1 year postoperatively. The 1-year TBR-positive segments showed a significantly higher facet union rate (83% vs. 57%, P=0.019) and less pseudoarthrosis (0% vs. 13%, P=0.041) at 2 years postoperatively. At 5 years postoperatively, 50% of the 2-year TBR-positive segments turned negative with solid intervertebral bony fusion. Conclusions: TBR-positive segments had significantly lower future VEC positivity, higher future facet union rates, and lower future pseudarthrosis rates. In LLIF-PSF, TBR suggests the establishment of intervertebral stability and allows consideration of intervertebral biomechanics.